Resiliência biocultural dos agroecossistemas na Amazônia: o baixo curso da bacia do ribeirão Taquaruçu Grande, Palmas-TO - Santos, Eliane Marques dos (Universidade Federal do Amazonas, 2018)
The Tocantins State has the totality of its territory inserted into the Brazilian Legal Amazon and it has in it the small stream of Taquaruçu Grande Basin in the city of Palmas, a region of agroecosystems of familiar production and biocultural diversity. However, these agroecosystems suffered such important modifications with the creation of Palmas that caused reorganization and systems adaptability. The main goal of this study was to analyse the biocultural modifications of these agroecosystems which provide the maintenance of the biocultural diversity and the resilience for the sustainability. This study was based on an integration of qualitative and quantitative with the theoretical methodology of dialectics of systemic complexity, resilience of socioecological systems, ethnoecology and transdisciplinarity. The data collected indicated the triggering events of the changes over the trajectory of the studied area and the impacts of external factors of a higher scale (regional and national) in which the focal system is related to higher and lower scales, changing its capability of adaptability and the system learning. In the complex of biologic-cultural, it was also noticed the following diversities: biological, cultural, agricultural and landscape which figure the wealth in socio-biodiversity of this region. The using system of the land is characterized by a long historical persistence and strong connection with the social and environmental system that it can produce. The productive processes and the local knowledge which leaded to the building of the landscape are responsible for the maintenance of local environmental diversity. The complex structure of the mosaic of the landscapes in these areas is an exemplar illustration of biocultural diversity. The resilience evaluation pointed out biocultural indicators in which the system kept itself resilient in the maintenance of biocultural diversity even after the occurred modifications caused by the urbanization, but, this resilience did not lead to sustainability of the agroecosystems with losing risk of local knowledge which were not transmitted across generations. For the sustainability it is necessary an adaptative management which includes the rational using of common goods and knowlege in order to create public policies towards local needs.